Autophagy Suppresses Tumorigenesis of Hepatitis B Virus-Associated Hepatocellular Carcinoma Through Degradation of MicroRNA-224 - Lan, Sheng-Hui (Hepatology, 2014)
In hepatocellular carcinoma (HCC), dysregulated expression of microRNA-224 (miR-224) and impaired autophagy have been reported separately. However, the relationship between them has not been explored. In this study we determined that autophagy is down-regulated and inversely correlated with miR-224 expression in hepatitis B virus (HBV)-associated HCC patient specimens. These results were confirmed in liver tumors of HBV X gene transgenic mice. Furthermore, miR-224 was preferentially recruited and degraded during autophagic progression demonstrated by real-time polymerase chain reaction and miRNA in situ hybridization electron microscopy after extraction of autophagosomes. Our in vitro study demonstrated that miR-224 played an oncogenic role in hepatoma cell migration and tumor formation through silencing its target gene Smad4. In HCC patients, the expression of low-Atg5, high-miR-224, and low-Smad4 showed significant correlation with HBV infection and a poor overall survival rate. Autophagy-mediated miR-224 degradation and liver tumor suppression were further confirmed by the autophagy inducer amiodarone and miR-224 antagonist using an orthotopic SD rat model. Conclusion: A noncanonical pathway links autophagy, miR-224, Smad4, and HBV-associated HCC. These findings open a new avenue for the treatment of HCC. (Hepatology 2014;59:505–517)